2006
DOI: 10.2202/1548-923x.1245
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem, Parent-Child Interaction, Emotional Support, and Self-Perception among Thai Undergraduate Nursing Students

Abstract: The purpose of this study was to examine the effect of parent-child interaction on self-esteem as mediated by emotional support and self-perception among undergraduate nursing students in Thailand. This study recruited 307 Thai baccalaureate nursing students who completed the Rosenberg Self-Esteem Scale, Ross Parent-Child Interaction Questionnaire, Emotional Support instrument, and Self-Perception questionnaire. Results revealed that the students reported relatively high self-esteem. A path model demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…A higher score indicates a higher level of depression. The CES-D has been translated into Thai for use in several studies with Thai participants [ 39 , 55 ]. The Cronbach's alpha of the CES-D for this study's sample was .87.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A higher score indicates a higher level of depression. The CES-D has been translated into Thai for use in several studies with Thai participants [ 39 , 55 ]. The Cronbach's alpha of the CES-D for this study's sample was .87.…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers reported a high prevalence of anxiety among nursing students in the United States and Iran [35–37]. Other studies found a high prevalence of depression among nursing students in Iran and Thailand [38, 39]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scale was previously used in nursing students by many authors. [9,13,14] Anxiety scale: Hamilton Anxiety Rating Scale (HAM-A) was one of the first rating scales developed to measure the severity of anxiety symptoms, and is still widely used today in both clinical and research settings. The scale consists of 14 items, each defined by a series of symptoms, and measures both psychic anxiety (mental agitation and psychological distress) and somatic anxiety (physical complaints related to anxiety).…”
Section: Tools For Data Collectionmentioning
confidence: 99%